Surface State Capture Cross-Section at the Interface between Silicon and Hafnium Oxide - Fu-Chien Chiu (Advances in Materials Science and Engineering)
The interfacial properties between silicon and hafnium oxide (HfO2) are explored by the gated-diode method and the subthreshold measurement. The density of interface-trapped charges, the current induced by surface defect centers, the surface recombination velocity, and the surface state capture cross-section are obtained in this work. Among the interfacial properties, the surface state capture cross-section is approximately constant even if the postdeposition annealing condition is changed. This effective capture cross-section of surface states is about 2.4 × 10−15 cm2, which may be an inherent nature in the HfO2/Si interface.